Pengembangan Pembelajaran Model BDR (Belajar di Rumah) untuk Meningkatkan Inovatif dan Kualitas Belajar Anak Usia Dini di Masa Pandemi Covid-19 - Indaria Tri Hariyani (JURNAL LENTERA ANAK, 2020)
This research departs from the problem of the still low quality of children's learning processes during the Covid-19 pandemic and the low ability of teachers to integrate character values in online learning. Under normal circumstances, BDR (Home Learning) and BDS (School Learning) models can be relatively the same in purpose and quality, the only difference may be the supporting facilities used. In an emergency, when students and teachers are still overshadowed by the deadly Covid-19 epidemic, the design and learning process that should be applied is different because learning can no longer be considered business as usual. Even so, the BDR policy which was decided with the aim of inhibiting the spread of the virus in practice must still refer to the national curriculum used. In the BDR model (Learning at Home) with the aim of helping early childhood to be able to find a better way of learning for themselves in every experience they learn. The BDR (Learning at Home) model is not carried out to determine the attainment level or the importance of the value (assigning grade) alone, but uses it as an aim to increase innovation and the quality of the learning process that has been experienced. This study aims to develop the BDR (Learning at Home) model of learning to improve the innovative and quality of early childhood learning during the Covid-19 pandemic. The development model used in this study is the Borg and Gall (2007) model which consists of ten steps. (1) Asses Needs To Identity Goal, (2) Conduct Instructional Analysis, (3) Analyze Learners And Context, (4) Write Performance Objectives, (5) Develop Assessment Instrument, (6) Develop Instructional Strategy, (7) Develop And Select Instructional Materials, (8) Design And Conduct Formative Evaluation Of Instruction, (9) Revise Instruction, (10) Design And Conduct Summative Evaluation. The product trial design in this study went through three stages, namely (a) expert validation, (b) small group trials, (c) large group trials. The results of the trial were then tested with the t test, which is to determine the innovative improvement and quality of early childhood learning from learning outcomes between using BDR model learning and not using BDR learning models. The results showed that BDR model learning can improve the innovative and quality of early childhood learning. From the results of data analysis obtained a significance value of 0.000 <0.005, then H0 is rejected. Thus it can be said that there is a difference in the average before and after treatment and the average score of the treatment before and after treatment on innovative and the quality of children's learning reduces failure in learning during the Covid-19 pandemic by using the BDR learning model that has been developed.